Childhood brain tumours, early infections and immune stimulation: A pooled analysis of the ESCALE and ESTELLE case-control studies (SFCE, France). (February 2018) - Lupatsch, Judith E.; Bailey, Helen D.; Lacour, Brigitte; Dufour, Christelle; Bertozzi, Anne-Isabelle; Leblond, Pierre; Faure-Conter, Cécile; Pellier, Isabelle; Freycon, Claire; Doz, François; Puget, Stéphanie; Ducassou, Stéphane; et al.
Highlights: We pooled data from two French case-control studies (469 cases and 2719 controls). Farm visits and contact with pets in early life were inversely associated with childhood brain tumours (CBT). Day-care in early life was not associated with CBT. A history of common infections or atopic conditions were not associated with CBT. Abstract: Background: Few studies have investigated whether early infections and factors potentially related to early immune stimulation might be involved in the aetiology of childhood brain tumours (CBT). In this study, we investigated the associations between CBT with early day-care attendance, history of early common infections, atopic conditions (asthma/wheezing, eczema, allergic rhinitis), early farm residence/visits and contact with animals. Methods: We pooled data from two nationwide French case-control studies, the ESCALE and ESTELLE studies. Children with a CBT diagnosed between 1 and 14 years of age were identified directly from the French National Registry of Childhood Cancers, while population controls were recruited from telephone subscribers. Odds-ratios (OR) and 95% confidence intervals (CI) were estimated using logistic regression adjusted for potential confounders. Results: The analyses included 469 cases and 2719 controls. We found no association between attending a day-care centre (OR: 0.9, 95%CI: 0.7–1.2) or having had repeated common infections (OR: 0.9, 95%CI: 0.7–1.2) in the first year of life and the risk of CBT. There was also no association with a history of asthma/wheezing (OR: 0.8, 95%CI: 0.56–1.1). Farm visits (OR: 0.6, 95%CI: 0.5–0.8) as well as contact with pets (OR: 0.8, 95%CI: 0.6–1.0) in the first year of life were inversely associated with CBT. Conclusions: Our findings suggest a protective effect of early farm visits and contact with pets, but not with other markers of early immune stimulation. This might be related to immune stimulation but needs further investigation.